Content and Context in Politics: A Scholars Views on Democracy in Islam - Mohammed, Yakubu; Gokaru, Shuaibu Umar (Journal Al-Muqaddimah, 2024)
Politics is a set of happenings that are linked with the governance of the people by the people for the people of a nation. Politics as it is an active practice in statements, manifestos, editorials, and philosophical texts, helps draw and redraw conceptual boundaries. To be sure, much of political life consists not in contesting formed concepts or constructing new ones, but in applying agreed-upon and cherished notions in new contexts to render unseen injustices visible or identifying additional examples of virtue, with varying success. Concepts are used in politics and reconfirmed as political concepts when they are mapped onto societal terrains in innovative and controversial ways. This paper aims at defining politics in its content and background in Islamic politics. The research adopted a qualitative approach to carry out this work. Hence, the work concealments the content and framework of politics by some scholars’ and Scholars’ views on democracy. This work covers how and where Islamic politics started and how politics penetrates Islam. The brief historical background of the Islamic political system, and how democracy infiltrates into Islam had been mentioned, as the scholars’ views on Islam and politics, this work is very important to the researchers, especially who wanted to study Islamic politics.